2019
DOI: 10.1021/acs.joc.9b00727
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid-Derived trans-N-Chloroformylimidazolidinones: Scalable, Stereoselective Synthesis, Structure, and Utility

Abstract: N-Acyl imidazolidinones, which are key intermediates in the stereoselective synthesis of amino acids by 'self-regeneration of stereochemistry' methods, are classically made by only moderately diastereoselective methods. We now report that cyclisation of pivaldimino-amides with phosgene in the presence of pyridine may be made fully diastereoselective for the trans-N-chloroformylimidazolidinones, and we detail the conformational features of the products. We show that despite the presence of the electrophilic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…It is encountered in several drugs, such as nilutamide, sorbinil, and nitrofurantoin, and constitutes a key molecular component of various agrochemicals . The nucleus also has synthetic versatility, for example, in the preparation of amino acids . Of particular interest are N -arylated hydantoins due to their important biological applications (Figure ).…”
mentioning
confidence: 99%
“…It is encountered in several drugs, such as nilutamide, sorbinil, and nitrofurantoin, and constitutes a key molecular component of various agrochemicals . The nucleus also has synthetic versatility, for example, in the preparation of amino acids . Of particular interest are N -arylated hydantoins due to their important biological applications (Figure ).…”
mentioning
confidence: 99%
“…1a ) that was formed cleanly by hydrogenolysis of 5 in THF. These conditions preserved the (surprisingly stable 15,16 ) carbamoyl chloride group. 17…”
Section: Resultsmentioning
confidence: 88%
“…1a) that was formed cleanly by hydrogenolysis of 5 in THF. These conditions preserved the (surprisingly stable 15,16 ) carbamoyl chloride group. 17 We found that heating 6 to 60 C for 72 h in the presence of Et 3 N and KI induced dearomatizing spirocyclisation to the dienone 7, a compound with clear structural homology to arogenate 1, in 82% yield.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…11 We recently reported a synthesis of the benzo-fused analogues of 3,4-dihydropyridin-2-onesnamely, 3,4-dihydroisoquinolinonesby an unusual version of the Bischler−Napieralski cyclization entailing the intramolecular KI-promoted Friedel−Crafts acylation of Nchloroformylimidazolidinones (see Scheme 1). 12 The starting materials for these reactions, imidazolidinone-derived carbamoyl chlorides carrying a 3-benzyl substituent, were formed diastereoselectively either directly from aromatic amino acids (for example, L-Phe) 12 or by stereoselective benzylation 13 of the stable enolates 14 of their N-chloroformyl substituted precursors. 15 We now show that 3,4-dihydropyridin-2-ones may likewise be formed by an intramolecular Friedel−Crafts reaction, from imidazolidinones bearing 3-allyl substituents.…”
mentioning
confidence: 99%